Effect of Annealing on Heavy-Load Wear Performance of Wear Resisting Steel–Carbon Steel–Cladded Plate. Issue 1 (2nd January 2021) - Liu, Pengtao; Ma, Lifeng; Zhi, Chenchen; Ma, Ziyong; Zhou, Cunlong; Zhao, Guanghui; Fan, Qinhong; Jia, Weitao
Abstract: The effect of annealing treatment on the wear performance of hot-rolled wear-resistant steel–carbon steel–cladded plates was investigated. A novel cladding procedure that can provide high wear resistance, a strong structure, and low cost is typically employed for metallurgical mining equipment, agricultural machinery, coal mining, and other industries. The cladded plates were first annealed at different temperatures and sampled for friction and wear experiments on an RETC MFT-5000 friction–wear tester and then an online 3D optical profiler was used to observe the wear tracks. Finally, the microstructure near the wear track was analyzed by using electron backscatter diffraction. The results show that the wear resistance of the BTW1/Q345R plate becomes weaker with an increase in temperature. Due to the properties of the plate, fluctuations still occur in the stable stage. At the annealing temperature of 860 °C, the cladded plate has the best wear resistance, which is proved with a maximum scratch width of 1.419 mm and a maximum scratch depth of 43.2 μm.